Best practice in cardiac anesthesia during the COVID-19 pandemic: Practical recommendations. Issue 3 (September 2020) - Moka, Eleni; Paladini, Antonella; Rekatsina, Martina; Urits, Ivan; Viswanath, Omar; Kaye, Alan D.; Pergolizzi, Joseph V.; Yeam, Cheng Teng; Varrassi, Giustino
Abstract : The COVID-19 outbreak has influenced the entire health care system, including cardiac surgery. In this review, the authors reveal practical aspects that are important during the COVID-19 pandemic with regards to the safe delivery of cardiac anesthesia. Timing for operations of the cardio-vascular system may be well programmed in most cases. Hence, the level of priorities must be defined for any single patient. The postponement of surgery may be convenient for most cases, if it is made in the best interest of the patient. The preanesthetic evaluation should be attentive of the respiratory history of the patient. Cardiac anesthesia always implies some respiratory monitoring; hence the existing clinical situation of the patient's respiratory system should be clear. In case of emergency surgery, the patient should be treated as if they potentially have or are at risk for the virus. In the case of a COVID-19 confirmed or suspected patient, attention must be made to preserve operating room and team integrity. The machineries are to be draped with plastic to simplify the disinfection after the operation. Perioperative management of suspected or confirmed COVID-19 patients must strictly follow the most relevant international guidelines. This review article has synthesized the common aspects present in the most important of these.